Pengaruh Indeks Pembangunan Manusia Terhadap Kemiskinan (Studi Kasus Pada Provinsi Jawa Barat) - Firman Kholiq; Deris Desmawan (Universitas Labuhanbatu, 2022)
The main problem facing developing countries is poverty. Poverty is a complex multidimensional problem, and therefore a focus of development. The purpose of this study was to analyze (1) the simultaneous effect of HDI level, education level, and unemployment on poverty in West Java, and (2) the partial effect of HDI level, education level, and unemployment poverty in the province. West Java. The research was conducted in the territory of the Unitary State of the Republic of Indonesia with a focus on West Java with data sources from the Central Statistics Agency (BPS). The data collection method used in this study is the observation method using multiple linear regression analysis techniques. The number of observations in 2017-2021 was 28 urban areas. The results showed that: (1) the unemployment rate, human development index and education level had a significant effect on poverty in Indonesia; (2) the unemployment rate has a significant positive effect on poverty in Indonesia; (3) education level has a significant effect. the impact of poverty in Indonesia. Positive and significant impact on poverty in Indonesia. (4) The Human Development Index has a negative and significant effect on poverty in Indonesia.